2020
DOI: 10.1111/jan.14646
|View full text |Cite
|
Sign up to set email alerts
|

Group‐randomized trial of tailored brief shared decision‐making to improve asthma control in urban black adults

Abstract: Aims To assess the intervention effects of BREATHE (BRief intervention to Evaluate Asthma THErapy), a novel brief shared decision‐making intervention and evaluate feasibility and acceptability of intervention procedures. Design Group‐randomized longitudinal pilot study. Methods In total, 80 adults with uncontrolled persistent asthma participated in a trial comparing BREATHE (N = 40) to a dose‐matched attention control intervention (N = 40). BREATHE is a one‐time shared decision‐making intervention delivered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In shared decision making, the patient or caregiver and the clinician discuss treatment options and their risks and benefits as well as the patient’s preferences, values, and lifestyle, with the aim of agreeing on a treatment that is best adapted to the patient while achieving their treatment goals. 23 Improved communication and shared decision making between health care professionals and patients with asthma or their caregivers has been shown to improve asthma control in a cross-sectional survey, 28 literature reviews, 29 , 30 a focus group study, 31 a group-randomized trial of a shared decision-making intervention, 32 and a cross-sectional analysis of audio-recorded medical consultations. 33 However, further investigation is needed because the results of the few randomized controlled studies performed so far have been mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In shared decision making, the patient or caregiver and the clinician discuss treatment options and their risks and benefits as well as the patient’s preferences, values, and lifestyle, with the aim of agreeing on a treatment that is best adapted to the patient while achieving their treatment goals. 23 Improved communication and shared decision making between health care professionals and patients with asthma or their caregivers has been shown to improve asthma control in a cross-sectional survey, 28 literature reviews, 29 , 30 a focus group study, 31 a group-randomized trial of a shared decision-making intervention, 32 and a cross-sectional analysis of audio-recorded medical consultations. 33 However, further investigation is needed because the results of the few randomized controlled studies performed so far have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a randomized clinical trial using BREATHE (BRief intervention to Evaluate Asthma THErapy), a shared decision making intervention, participants included in shared decision making with their physician had better asthma control and reduced symptoms at follow-up compared to participants who received a control intervention. 32 Additionally, asthma control could be improved if health care professionals clearly communicate to patients the benefits of pairing ICS with a fast-acting bronchodilator for rescue treatment, as recommended in the newest treatment guidelines. 2 These guidelines should be discussed during shared decision making, which should take into account treatment efficacy and patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…As such, shared decision-making (SDM), as the concept suggests, is an attempt to incorporate the patient’s views into decisions about the medical management of a complaint, symptom, or disease. It is ‘a patient engagement model that includes strategies that promote patient and clinician engagement to jointly consider management options … the clinician’s role is to facilitate discussion of the risks and merits associated with options, the goal of reconciling differences.’ (George et al, 2021 , p. 1502).…”
Section: Behaviour As the Central Outcome In Health Care (Kaplan ...mentioning
confidence: 98%
“…The selected studies reported on a broad variety of conditions: oncology [33,35,45,47,49,[64][65][66]69,86,90,91], musculoskeletal disorders [34,40,42,44,48,50,55,81,84,87], cardiovascular disease [36,[51][52][53]70,78,93,94], general practice consultations [68,71,73,75,80,83,95], mental disorders [32,39,41,60,61,82], diabetes mellitus type II [37,43,46], elective otolaryngologic surgery [72,88,92], asthma [57,…”
Section: Study Participantsmentioning
confidence: 99%